Robotic Assistance of Human Motion Using Active-Backdrivability on a Geared Electromagnetic Motor. (1st March 2016) - Claros, Mario Jorge; Soto, Rogelio; Gordillo, Jose Luis; Pons, Jose Luis; Contreras-Vidal, Jose Luis
In this research, we describe an actuation and control system designed for geared electromagnetic motors, which is characterized by its simple implementation, fast response to external input loads, reliable human-machine interaction features, no need for previous set-up or calibration from user to user and high portability due to the reduction of weight and space used. By the implementation of the proposed system, an electromagnetic motor can become a multitasking, wearable actuation system capable of: detecting the user's intentions regarding motion, tracking the limbs with minimal force interaction within a wide bandwidth and also providing controllable assistance and resistance forces to the user's movements, without the use of any biological signal. Validation of the proposed approach is shown by the construction of a powered orthosis for the knee, used to test the system's performance under real human motion conditions. The proposed system was tested on one healthy subject by measuring electromyographic levels both with and without the orthosis, under controlled flexion and extension cycles. Experimental results demonstrate the effectiveness of the proposed approach in detecting the user's intentions regarding motion, reducing and increasing muscular activity when configured for assistance and resistance, respectively, and also increasing the transparency of the actuation system when perfect tracking of the limbs is needed.